Multimodalidade E Hipertextualidade: Caminhos Para Pesquisa E Ensino (PERcursos Linguísticos, 2021)
In this work, based on the understanding that every text is multimodal and also a hypertext, we seek to weave some reflections around the contributions of Multimodal Social Semiotics, anchored in the studies by Kress (2010, 2011, 2015), from Textual Linguistics through Koch (2005) and Xavier (2002) studies to think about text and hypertextuality. Thus, we discuss issues such as (a) the conceptual dimensions between text, hypertext and multimodality; (b) how to think about the methodological paths that can be followed for the development of research and (c) highlight aspects that need to be observed and considered in multimodal analyzes. From these reflections we seek to demarcate how these notions intertwine and are interdependent in the process of production and reception of texts, so relevant today.